ANALISIS KEKUATAN DAN DAYA DUKUNG TANAH LEMPUNG YANG DISTABILISASI ASPAL EMULSI - YUs Yudhiantoro (Jurnal Teknik Sipil, 2014)
ABSTRAK Soil is not always suitable be a place to build a construction or be a raw material construction because the most of soil have limited strength and bearing capacity. One of cause is volume changes; generally happened because there are swelling and shrinkage of clay soil together with drying and wetting in natural process automatically in a whole year. This study aims to determine the effect of Cationic Asphalt Emulsion, also called Asphalt Emulsion (AE),in strength and CBR (California Bearing Ratio) of clay soil. The disturbed of clay soil obtained from Desa Doy, Kecamatan UleeKareng, Banda Aceh and AE derived from PT. Hutama Prima, Cilacap, Jawa Tengah. Tests conducted by ASTM (American Standard Testing and Materials) which includes testing of compaction (Standard Proctor method)and CBR laboratory. The results showed that stabilization of optimum AE increase compression strength (qumaks) and CBR value, both of soaked and unsoaked. Value of optimum AE for maximum dry density is 7-10%, for compressive strength at optimum Proctor condition is 4-6% and for CBR value 2-3% (soaked) and 8-9% (unsoaked) at optimum Proctorcondition. Kata kunci : asphalt emulsion, compressive strength, CBR value, stabilization